Growth of the management in batch system in the west part of France: Results of the artificial insemination realized in 1999 with sperm from a specialized center - Colin M.; Roux J.F.; Pomies N.; Chwalowska P.; Breton Le G. (2. International Conference on Rabbit Production in Hot Climates, 1999)
This work presents the 1997 practical results of a specialized Rabbit artificial insemination center (300 000 AI carried out from its creation in 1995). Fertility and prolificacy are at the same level than the ones obtained through natural mating. Variability within the farm is very high. The results are not affected significantly by the size of the farm, the type of Management or the month. These results confirm that today it is possible to produce semen in a specialized Rabbit artificial insemination center and to carry out distribution to commercial rabbit farms.
2. International Conference on Rabbit Production in Hot Climates, 1998/09/07-09, Adana (Turkey)